The Effectiveness of Contextual Teaching and Learning Approach in Enhancing Indonesian EFL Secondary Learners’ Narrative Writing Skill - Jubhari, Yuriatson; Sasabone, Luana; Nurliah, Nurliah (REiLA : Journal of Research and Innovation in Language, 2022)
This study investigates the effectiveness of the Contextual Teaching and Learning (CTL) approach in enhancing Indonesian EFL secondary learners’ narrative writing skills and the perception of Indonesian EFL secondary schools toward applying the CTL approach. This study employed a quasi-experimental design with fifty-two eleventh-grade students as participants. The participants were divided into two groups; An experimental group received the CTL approach, and a control group received the conventional way. This study utilized a pre-posttest and perceptional questionnaire. Nonparametric tests (i.e., Mann-Whitney U test and Wilcoxon test) were run to analyze the data in this study. The Man-Whitney U test indicated a significant difference between the mean score for the experimental group with the CTL approach and the control group without the CTL approach (9.86 > 10.12). Meanwhile, the Wilcoxon test illustrated that the leading score of the pre-test (10.14) and the post-test (16.05) in the experimental group differ significantly. Implementation of the CTL approach through its components positively contributes to teaching narrative writing skills. Meanwhile, the perceptional questionnaires showed that the students' experiment group perceived the implementation of the CTL Approach positively. This study results render teachers’ insight into a practical approach to teaching writing to be able to teach narrative writing.